Living support characteristics among mentally healthy elderly: a state-wide descriptive study in Malaysia - Aniza, Abd Aziz; Khairi, Che Mat; Samhani, Ismail (2020)
Background: Despite the physiological losses and the psychosocial stresses related to agerelated diseases, some elderly still able to manage them successfully which lower their psychological distress. This study aims to describe the pattern of living support characteristics among the mentally healthy elderly in a state in Malaysia East Coast. Materials and Methods: A state-wide community based cross-sectional study focusing on the elderly with the mentally stable state, having normal/mild cognitive function with satisfactory social skill was conducted. A cluster random sampling technique was applied, and the interviewer guided questionnaire by using a standard proforma was utilized to collect the demographic, physical health, and living support data. Result: This study included 1013 elderly, majority (86.4%) were young elderly aged between 60 and 74 years with almost equal males and females. The living support sub-domains were presented into social support, economic, and physical living support. They demonstrated a sufficient economic backup where almost all of them own some property despite low monthly income. Further, they were socially well supported, as 90.6% of them reported living with families even though most of them were single and widowed and 90.3% of them having caregivers to take care of them if they are ill. Besides, most mentally healthy agers reported live in a safe living environment (96.1%). Our study also discovered about three-quarter of our respondents used social media; mainly WhatsApp and Facebook. Conclusion: The present study revealed a few important living support elements among mentally healthy elders in the local setting. Despite having a low monthly income, the older persons with good mental health in this study own some assets at a late age. They lived with their family who acts as a caregiver at any time when they are sick and secured with safe living hood and had fair access to mobile communications. These characteristics should be examined further to prove their influence on geriatric mental health.